Compositional Characteristics of Sulfur-Containing Compounds in High Sulfur Coals. Issue 2 (June 2014) - Zhao, Qiaojing; Tang, Yuegang; Li, Weiwei; Wang, Shaoqing; Deng, Xiujie; Yu, Xiaolei
The geochemistry of high-organic-sulfur coals of different ranks from three coalfields in China, Chenxi, Hunan Province, Guiding, Guizhou Province, and Hedong, Shanxi Province have been studied using Soxhlet extraction, gas chromatography and gas chromatography-mass spectrometry. The random vitrinite reflectances of Chenxi, Guiding, and Hedong coals are 0.77%, 1.29% and 1.41%, respectively. Organic sulfur contents, on dry and ash-free basis, are 10.06%, 10.26% and 3.51%, respectively. The So /St ratio is 95%, 93% and 87%, respectively. Three types of sulfur-containing compounds were identified in coals, dibenzothiophene series, benzonaphthothiophene series, and benzobisbenzothiophene series. No benzobisbenzothiophene series was identified in the Guiding and Hedong coal. As the coal rank of a sample increased, so did the content of dibenzothiophene series; in contrast, the benzonaphthothiophene series showed a decreasing trend. The substituent group was mainly methyl. The coal-forming environments, organic sulfur contents and coal rank all played an important role in the types of organic sulfur-containing compounds.